Studi Empiris Pengaruh Beban Kerja dan Kepuasan Kerja terhadap Kinerja Karyawan UKM di Surabaya: An Empirical Study of the Effect of Workload and Job Satisfaction on the Performance of SME Employees in Surabaya - Hariputra, Akbar; Rachmadhan, Aditya Arief; Sastryawanto, Hary (Jurnal Ilmiah Manajemen Agribisnis, 2025)
This study aims to analyze the influence of workload and job satisfaction on employee performance in Small and Medium Enterprises (SMEs) in the food and beverage industry in Surabaya. This study used a quantitative approach with an explanatory design and involved 200 respondents selected through purposive sampling. Data analysis was conducted using multiple linear regression. The results showed that workload had a negative and significant effect on employee performance, while job satisfaction had a positive and significant effect on employee performance. The regression model showed that both independent variables explained 44.7% of the variation in employee performance. These findings support the Job Demands-Resources model and emphasize the importance of workload management and job satisfaction enhancement to drive optimal performance in SMEs.